Innovative community‐based educational face‐to‐face intervention to reduce HIV, hepatitis C virus and other blood‐borne infectious risks in difficult‐to‐reach people who inject drugs: results from the ANRS–AERLI intervention study. (28th September 2015) - Roux, Perrine; Le Gall, Jean‐Marie; Debrus, Marie; Protopopescu, Camélia; Ndiaye, Khadim; Demoulin, Baptiste; Lions, Caroline; Haas, Aurelie; Mora, Marion; Spire, Bruno; Suzan‐Monti, Marie; Carrieri, Maria Patrizia
Abstract: Aims: To study the effectiveness of an educational intervention on risks associated with drug injection, comparing primary [unsafe HIV–hepatitis C virus (HCV) practices] and secondary (local complications at injecting site) end‐points in harm reduction (HR) programmes offering this intervention versus HR programmes not offering it. Design: This non‐random clustered intervention study was conducted in nine intervention groups (programmes offering the intervention) and eight control groups (programmes not offering it). Each participant was followed‐up through a telephone interview at enrolment and at 6 and 12 months. Setting: The study took place in 17 cities throughout France. Participants: Of the 271 participants, 144 were enrolled into the intervention group and 127 in the control group. Of the latter, 113 received at least one educational session. Intervention: A series of participant‐centred face‐to‐face educational sessions. Each session included direct observation by trained non‐governmental organization (NGO) staff or volunteers of participants' self‐injecting the psychoactive product they used habitually; analysis by the trained NGO staff or volunteers of the participant's injecting practices, identification of injection‐related risks and explanation of safer injecting practices; and an educational exchange on the individual participant's injection practices and the questions he or she asked. Measurements: Primary and secondary outcomes were 'at least one unsafe HIV–HCV practice' and at least one injection‐related complication (derived from a checklist). Findings: The proportion of participants with at least one unsafe HIV–HCV practice in the intervention group decreased significantly, from 44% at M0 to 25% at M6, as well as complications at the injection site (from 66 to 39% at M12), while in the control group it remained mainly stable. Multivariate probit analyses showed that the intervention group experienced a significant reduction in unsafe HIV–HCV practices at M6 [coefficient, 95% confidence interval (CI) = −0.73 (−1.47 to 0.01)] and in injection‐related complications at M12 [coefficient, 95% CI = −1.01 (−1.77 to −0.24)], compared with the control group. Conclusions: An inexpensive and easily implemented educational intervention on risks associated with drug injection reduces significantly unsafe HIV–HCV transmission practices and injection‐related complications.